An exploration of exposure to river flood risk in Spain using the National Floodplain Mapping System. - Canovas García, Fulgencio; Vargas Molina, Jesús (Taylor & Francis, 2024)
In Spain, human exposure to flooding continues to increase driven by changes in land use and population growth in urban and coastal areas. This study explores the geography of flood exposure in Spain in relation to human population, economic activities and points of special significance. The analysis is based on public flood hazard and risk mapping generated by water management administrators at the river basin district level. The data are published and accessible through the Spanish National Floodplain Mapping System (NFMS). The results show for first time, the spatial distribution of human population exposure, which amounts to at least 3,263,000 inhabitants nationwide (6.9% of the total Spanish population), the potential economic loss, totalling at least 122,132 million euros across Spain, and points of special significance classified into eleven different categories that have been analysed for all Spanish river basin districts. The results also indicate a higher exposure concentration along the Mediterranean coast.
Keywords: Inundaciones - Previsiones - España; Catástrofes naturales - Prevención y control; Sistema Nacional de Cartografía de Zonas Inundables; Cartography; Exposure; Flood; River basin district; EU Floods Directive